Takayasu’s arteritis: a diagnostic dilemma - Kaur, Sukhdeep; Kaur, Avneet; Sharma, Aditi; Rai, Seema (International Journal of Research in Medical Sciences, 2025)
Takayasu`s arteritis is an uncommon form of chronic vasculitis that primarily affects medium and large blood vessels, including the aorta and its major branches. The disease is mainly seen in young women. This is marked by mononuclear cell infiltration and granulomatous inflammation within the vascular media. These pathological changes result in thickening of the arterial wall, which can lead to stenosis, occlusion, or the formation of aneurysms. It can lead to severe complications such as stroke, ischaemic heart disease, pulmonary hypertension, secondary hypertension and aneurysm formation. Here we present a case of Takayasu`s arteritis in a 10-year-old girl who presented with low grade fever, headache and systemic hypertension with thickened walls of left subclavian artery and left renal artery in computed tomography angiogram. Early diagnosis and prompt treatment are crucial for managing Takayasu`s arteritis. When the disease is in a dormant phase, the prognosis tends to be more favourable.